Measuring resonances of the vocal tract using frequency sweeps at the lips - Ahmadi, Farzaneh (2013)
Precise measurement of the resonances of the human vocal tract is important in the research of acoustical phonetics. It has also significant applications in speech therapy and language learning - providing feedback about the shape of the vocal tract and position of the tongue. This paper investigates a novel method of measuring these resonances using linear frequency sweeps at the lips. To investigate the effectiveness of the method, tests have been completed on constructed tube models of the vocal tract and also human subjects for six English vowels. The precision of the measurement in the current implementation is shown to be superior compared to traditional electro-larynx method.